Why cultural studies? - Rodman, Gilbert B., 1965- (Malden, MA ; Chichester, West Sussex : Wiley Blackwell, 2014)
Why Cultural Studies? is a rallying call for a reinvigoration of the project of cultural studies that provides a critical analysis of its meteoric rise to the academic fore and makes a convincing argument for the pressing need for a renewed investment in, and re-evaluation of, its core ideals. Rodman argues that there are valuable lessons we can learn from cultural studies' past that have the potential to lead cultural studies to an invigorated and viable futureMakes the claim that cultural studies isn't - and shouldn't be - solely an academic subject, but open to both academics and non-acade.
Preface -- Acknowledgements -- Cultural studies: what's the point? -- Cultural studies: what it is -- Cultural studies: what's wrong -- Cultural studies: what it was -- Cultural studies: what next? -- References -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Culture -- Study and teaching; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Culture -- Study and teaching; Electronic books; Electronic books